First discovery of Quercus-feeding Nepticulidae (Lepidoptera) in South America, with description of new species and designation of the S. nigriverticella complex in the S. saginella group - Remeikis, Andrius; Stonis, Jonas R. (Zootaxa, 2015)
We describe three new species: Stigmella crassifoliae Remeikis & Stonis, sp. nov. (a leaf-miner on Quercus crassifolia and Q. crispipilis from the highlands of Guatemala), S. robleae Remeikis & Stonis, sp. nov., and S. humboldti Remeikis & Stonis, sp. nov. (leaf-miners on Quercus humboldtii from the Colombian Andes). No Quercus-feeding Nepticulidae species were previously known from South America. All new species are illustrated with photographs of the leaf-mines, cocoons, adults, and genitalia. In the S. saginella species group, for the species possessing in male genitalia M-shaped gnathos with caudal processes closely juxtaposed and phallus without cornuti, a new species complex (the S. nigriverticella complex) is defined. We also provide a pictorial key to the species of the new complex.